2011
DOI: 10.1002/adma.201004676
|View full text |Cite
|
Sign up to set email alerts
|

One‐Dimensional Nanostructures of Ferroelectric Perovskites

Abstract: Nanorods, nanowires, and nanotubes of ferroelectric perovskites have recently been studied with increasing intensity due to their potential use in non-volatile ferroelectric random access memory, nano-electromechanical systems, energy-harvesting devices, advanced sensors, and in photocatalysis. This Review summarizes the current status of these 1D nanostructures and gives a critical overview of synthesis routes with emphasis on chemical methods. The ferroelectric and piezoelectric properties of the 1D nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
206
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(208 citation statements)
references
References 359 publications
(262 reference statements)
2
206
0
Order By: Relevance
“…To achieve high‐output PNGs, endeavors have been employed in exploring anisotropic piezoelectric materials such as nanowires11, 12, 13, 14, 15, 16 and nanosheets,17, 18 which show more outstanding performance compared with the traditionally used isotropic ones 19, 20, 21, 22, 23, 24. Among such materials, lead‐free (Na,K)NbO 3 (KNN) nanowires (NWs) with remarkable piezoelectric property and biocompatibility25, 26, 27, 28 serve as one of the most attractive candidates, which are seldom studied in flexible PNG fabricating till now. Despite the pursuit of noteworthy anisotropic piezoelectric materials, highly oriented arrangement of the anisotropic piezoelectric materials29, 30, 31 and patterned structure of the device's piezoelectric layer,32, 33 both of which can significantly improve the electrical output of the PNGs, are also highly required.…”
mentioning
confidence: 99%
“…To achieve high‐output PNGs, endeavors have been employed in exploring anisotropic piezoelectric materials such as nanowires11, 12, 13, 14, 15, 16 and nanosheets,17, 18 which show more outstanding performance compared with the traditionally used isotropic ones 19, 20, 21, 22, 23, 24. Among such materials, lead‐free (Na,K)NbO 3 (KNN) nanowires (NWs) with remarkable piezoelectric property and biocompatibility25, 26, 27, 28 serve as one of the most attractive candidates, which are seldom studied in flexible PNG fabricating till now. Despite the pursuit of noteworthy anisotropic piezoelectric materials, highly oriented arrangement of the anisotropic piezoelectric materials29, 30, 31 and patterned structure of the device's piezoelectric layer,32, 33 both of which can significantly improve the electrical output of the PNGs, are also highly required.…”
mentioning
confidence: 99%
“…The on-going dimensional downscaling of materials, to cram more components onto integrated circuits, in turn gives a great boost to the evolution of potential nanostructured ferroelectric materials and devices. [12][13][14][15][16][17][18][19][20][21] For instance, memory 40 storage based on ferroelectric polarisation reversal has been predicted as one of the emerging memory technologies 12 , owing to their high read-write speed, low power consumption and long rewriting endurance. 27,28 Size and dimensionality plays a critical role in determining the 45 ferroelectric characteristics of a material at the nanoscale, due to the different ways in which dipoles align in ferroelectric crystals.…”
Section: Nanoscale Ferroelectrics and Piezoelectricsmentioning
confidence: 99%
“…144 This crystal 55 engineering strategy has been successfully applied to the hydrothermal synthesis of dodecahedral shaped BaTiO3 nanoparticles (Figure 2(c)), through the selective adsorption of polyethylene glycol (PEG) moieties onto the {110} surface facets of BaTiO3. 60 Adireddy et al 61 have also reported the controlled 60 solvothermal synthesis of monodisperse, free-standing, BaTiO3 nanocubes with a mean diameter 20 nm (Figure 2(b) 1D ferroelectric nanostructures (nanowires, rods, tubes, belts) are the most extensively studied nanostructures due to their sizedriven ferroelectric behaviour 17,19 Among the 1D ferroelectrics, pervoskite-structured ternary oxides of ABO3 type, e.g. BaTiO3, PbZr1-xTixO3, SrTiO3, are the most extensively investigated 85 material due to their excellent ferroelectric characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, BT sheets (with micrometer-order thickness) are applied for multilayered ceramic capacitors (MLCC) and positive temperature coefficient (PTC) thermistors. BT fibers will be applied for non-volatile ferroelectric random access memories (FeRAM) and nano-electromechanical systems (NEMS) [4,5].…”
Section: Introductionmentioning
confidence: 99%